2006
DOI: 10.2217/14796694.2.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Hereditary Diffuse Gastric Cancer: Progress and Future Challenges

Abstract: Hereditary diffuse gastric cancer (HDGC) is a rare cancer susceptibility syndrome. One third of HDGC syndrome families carry germline mutations of the E-cadherin gene. Owing to the limitation of the current endoscopic screening techniques and since no chemoprevention is yet available, total prophylactic gastrectomy is the only option offered to carriers of inactivating mutations in genetic counseling. In this regard, 30% of the E-cadherin germline mutations reported to date are of the missense type, and since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Additionally, the prevalence of mutations in patients without a family history of GC was unknown; thus, the IGCLC believed it was premature to offer genetic testing for sporadic cases [3]. Since then, the prevalence of CDH1 mutations in families with a history of lobular breast cancer and/or colon cancer, as well as the prevalence of CDH1 mutations among young individuals with GC and no family history of the disease from low-incidence populations, has been documented and the criteria for CDH1 testing have been modified [5,7,8,11,[15][16][17][18] (Table 1). We found that patients with a family history of GC (histology unknown) and documented DGC who tested positive for CDH1 mutations also had a family history of breast cancer and/or colon cancer ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the prevalence of mutations in patients without a family history of GC was unknown; thus, the IGCLC believed it was premature to offer genetic testing for sporadic cases [3]. Since then, the prevalence of CDH1 mutations in families with a history of lobular breast cancer and/or colon cancer, as well as the prevalence of CDH1 mutations among young individuals with GC and no family history of the disease from low-incidence populations, has been documented and the criteria for CDH1 testing have been modified [5,7,8,11,[15][16][17][18] (Table 1). We found that patients with a family history of GC (histology unknown) and documented DGC who tested positive for CDH1 mutations also had a family history of breast cancer and/or colon cancer ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A negative test result does not mean the patient will not develop GC [3]. These patients should still be followed up with gastric screening similar to that done in at-risk families, as it is possible a mutation exists in the CDH1 gene that has not yet been discovered [7]. Currently, all patients who have undergone a prophylactic gastrectomy despite a negative test result (or prior to determining the results of CDH1 screening) have been deemed negative for cancer upon histological examination (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations